Illness, Narration and Healing: Women’s Perspectives - Certini, Rossella (Studi sulla Formazione/Open Journal of Education, 2019)
The history of the illness is linked to the history of suffering and pain. Every historical period, every human event has been characterized by the explicit expression of ever new "pathologies" which over time have diversified and multiplied. Illness and suffering are not an "exasperation of sensations", but tell the story of a body and a mind that together go through a multitude of experiences and try to reconstruct the meaning of a human story condemned by illness and, perhaps, to death. The meaning of the illness pass primarily through the "word" and there are many narrative strategies used to tell the painful experience that becomes a shared emotional experience. The female narrative is examined here as a research paradigm and the inner and emotional dynamics are highlighted. Self-care through storytelling